Pengaruh Earning Per Share, Price to Book Value, Trade Volume, dan Market Cap terhadap Return Saham pada Perusahaan Mineral Energi yang Listing pada Bursa Efek Indonesia Periode 2019-2023 - Ali Marwan; Vidya Amalia Rismanty (Yayasan Sahabat Cendekia Jaya, 2024)
Purpose. The purpose of this research is to calculate how much influence Earning Per Share, Price to Book Value, Trade Volume and Market Cap partially or simultaneously have on share returns in companies belonging to the energy mineral sector that have been listed on the Indonesia Stock Exchange in the 2019-2023 period. Methods. This research is a qualitative research type. The sample used was taken using the purpose sampling method and eliminated outlier data so that 11 companies were obtained with a time span of 5 years, so the data used in the research was 55 sample data. Results. Simultaneous research results using the F test show that investment profits as measured by Earning Per Share, Price to Book Value, Trade Volume and Market Cap are able to significantly influence stock returns. Partially, using the t test, it shows that changes in Earning Per Share, Price to Book Value, Trade Volume are able to significantly influence the value of stock returns, while Market Cap is not able to significantly influence stock returns. The results of the coefficient of determination with a value of adjusted R square of 0.488 or 49%, which concluded that the dependent variable in this study was able to have an influence of 49% on the independent variable, namely stock returns with 51% being influenced by other variables outside this research. Implications. This research shows that the Trade Volume variable is able to provide the greatest influence on stock returns. Keywords. Earning Per Share; Price to Book Value; Trade Volume; Market Cap; Return.